Osteo-radio-necrosis (ORN) and bisphosphonate-related osteonecrosis of the jaws (BRONJ): the histopathological differences under the clinical similarities - Mitsimponas, Konstantinos; Moebius, Patrick; Amann, Kerstin Ute; Stockmann, Philipp; Schlegel, Karl-Andreas; Neukam, Friedrich Wilhelm; Wehrhan, Falk (International Journal of Clinical and Experimental Pathology, 2014)
Both Osteoradionecrosis (ORN) and Bisphosphonate associated osteonecrosis of the jaws (BRONJ) present clinically as regions of exposed necrotic bone. The study aimed to demonstrate the histopathological differences behind the observed clinical similarities.Ten ORN specimens and ten BRONJ specimens were used, as well as ten samples of normal mandibular bone as control. Two bone-specific stainings were used, i.e. Sirius Red for the study of the relative presence of collagen types I and III and toluidine blue for the study the osteon density.The Red Green Blue (RGB)-analysis of the specimens stained with Sirius Red identified significant differences between the chromatic patterns observed in bone preparations of patients suffering from ORN when compared to both BRONJ and control samples. Moreover, the osteon density of the BRONJ samples was significantly lower when compared to ORN and normal bone samples.The demonstrated differences in the bone architecture and in the bone collagen content between the two pathological conditions most likely reflect underlying pathophysiological differences.
EVALuna2:24379